Chemical properties analysis of liquid and semi-solid bioconversion products from organic waste and their effects on soil fertility and sweet corn yield - Emma Trinurani Sofyan; Stefina Liana Sari; Saefur Rohman; Indra Permana; Rahmat Budiarto; Mansour Ghorbanpour; Sastrika Anindita (Universitas Sebelas Maret, 2025)
Food security remains a critical global challenge, particularly as land degradation, driven by excessive use of synthetic fertilizers, continues to threaten soil fertility and crop productivity. This study aimed to evaluate the characteristics of liquid and semi-solid fermented organic waste and their effects on several soil chemical properties and sweet corn yield. The experiment was conducted in a corn field in Pagerwangi Village, West Java, Indonesia. The experiment used a Split-Plot Design with three replications. The main plot was the fermented waste product treatment, which consisted of three levels: no product (A0), liquid product (A1), and semi-solid product (A2). The subplot was the N-P-K dose level, which consisted of four levels: 0 N-P-K (a0), 1/2 N-P-K dose (a1), 3/4 N-P-K dose (a2), and standard N-P-K dose (a3). The research findings indicated that the macro and microelements present in semi-solid products were several times higher compared to liquid ones. Furthermore, the microbial population in semi-solid products exhibited higher density compared to liquid products. Field tests also demonstrated that both liquid product (A1) and semi-solid product (A2) significantly increased total nitrogen, organic-C, and soil pH compared to the control (A0). The highest sweet corn productivity was observed in treatment A2, with a yield increase of 47.62% compared to the control. The research results suggested that the use of fermented organic waste products could enhance soil fertility and sweet corn production.